INTERACTION ENTRE LES SPORTS ET LA POLITIQUE : Stratégie de positionnement politique des leaders sportifs à Kisangani - NSOBA, Ludovic MBAYA; KASASA, Gilbert MISAKO; TOBO, Luvince MBAYA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Nowadays, football, which is one sport among many others, is, without a single mistake, a sport draining thousands of people. Beyond that, football also has an educational character. It should be noted that the history of football dates back to the period of the 19th century. Probably from China, football was reduced before the second half of the 19th century to a ball game with mythical warlike or playful meanings. But today, he conquered the world. After World War I, the era of football’s cosmopolitanism will turn into an era of nationalism. Hence football’s interaction with politics. Indeed, it is observed that in the Democratic Republic of Congo, football has become a springboard for some political leaders. It contributes more to the emergence of politicians in the DRC in general and those of the City of Kisangani in Tshopo Province in particular. Some leaders of Congolese football companies become deputies either at the provincial level or at the national level. Some, thanks to their sports training, are running as candidates or even for the presidential election and capturing considerable votes. The eloquent examples pinned down in this article may serve as inspiration for others.